Examination of the physical state of the soil under conventional and reduced tillage systems - Tuba, Géza (Acta Agraria Debreceniensis, 2013)
he effect of reduced and conventional tillage systems on soil compaction and moisture content in two years with extreme weather conditions is introduced in this paper. The investigations were carried out in a long-term soil cultivation experiment set on a heavy textured meadow chernozem soil at the Karcag Research Institute. In 2010 the amount of precipitation during the vegetation period of winter wheat was 623.3 mm, 2.2 times higher than the 50-year average, while in 2011 this value was 188.7 mm giving only 65% of the average. The examinations were made after harvest on stubbles on 4 test plots in 5 replications in the case of each tillage system. Soil compaction was characterised by penetration resistance values, while the actual soil moisture contents were determined by gravimetry. The values of penetration resistance and soil moisture content of the cultivated soil layer were better in the case of reduced tillage under extreme precipitation conditions. It could be established that regular application of deep soil loosening is essential due to the formation of the unfavourable compact soil layer under 30 cm. Conventional tillage resulted in enhanced compaction under the depth of ploughing, the penetration resistance can reach the value of 4 MPa under wet, while even 8 MPa under dry soil status.